2021
DOI: 10.1111/mec.16062
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic and major‐locus contributions to sexual maturation timing in Atlantic salmon

Abstract: Sexual maturation timing is a life‐history trait central to the balance between mortality and reproduction. Maturation may be triggered when an underlying compound trait, called liability, exceeds a threshold. In many different species and especially fishes, this liability is approximated by growth and body condition. However, environmental vs. genetic contributions either directly or via growth and body condition to maturation timing remain unclear. Uncertainty exists also because the maturation process can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
107
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 87 publications
16
107
4
Order By: Relevance
“…which relates to higher condition, is also associated with increased migration activity while in males, the vgll3*L allele, which relates to lower condition, is associated with higher migration activity. Interestingly, body condition has been suggested to, at least partly, be a factor contributing to the detected vgll3 effects on maturation timing of male parr (Debes et al 2021). Our results add more evidence supporting the notion that vgll3 effects on trait expression might be mediated by body condition, although more research on the topic is needed.…”
Section: Potential Mechanisms Explaining Variation In Migration Activity Linked To Vgll3supporting
confidence: 65%
See 1 more Smart Citation
“…which relates to higher condition, is also associated with increased migration activity while in males, the vgll3*L allele, which relates to lower condition, is associated with higher migration activity. Interestingly, body condition has been suggested to, at least partly, be a factor contributing to the detected vgll3 effects on maturation timing of male parr (Debes et al 2021). Our results add more evidence supporting the notion that vgll3 effects on trait expression might be mediated by body condition, although more research on the topic is needed.…”
Section: Potential Mechanisms Explaining Variation In Migration Activity Linked To Vgll3supporting
confidence: 65%
“…For example, in Atlantic salmon (Salmo salar), variation in a genome region including the vestigial-like family member 3 gene (vgll3) on chromosome 25 has been shown to explain a large proportion of variation in the sea-age at maturity in males and females (Barson et al 2015). Since vgll3 is involved in fat cell regulation (Halperin et al 2013), potentially controlling resource allocation between energy reserves and somatic growth, and its effects are at least partially phylogenetically conserved, it potentially contributes to moderating the expression of life-history strategies across species (Debes et al 2021). Indeed, vgll3 is associated with size, as well as age, at maturity in both salmon and humans (Cousminer et al 2013;Barson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not detect any difference in either SMR or body condition between juvenile Atlantic salmon individuals of different homozygous vgll3 genotypes. The lack of difference in body condition might be related to body size or life-stage; the fish in the study by Debes et al (2021) were considerably more developmentally advanced, averaging 19 g, and had been reared for approximately 3100 degree days at stable daily temperatures with many of the males maturing the same autumn. In comparison, the fish in this study averaged just 1.08 g and had been reared at approximately 1900 degree days and also under a variable temperature regime, which could have further reduced growth (Imholt et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Vgll3 genotype has been shown to have a strong effect on salmon life-history (Ayllon et al, 2015;Barson et al, 2015;Verta et al, 2020), and recent findings have suggested that this effect might be mediated by vgll3-induced differences in body condition (Debes et al, 2021). Taking this together with the connections between standard metabolic rate (SMR) and resource acquisition and assimilation (Armstrong et al, 2011;Auer, Bassar, et al, 2020;Auer, Solowey, et al, 2020;Bochdansky et al, 2005;Millidine et al, 2009;Rosenfeld et al, 2015), we hypothesized that vgll3 genotype might be asserting some of its effects through changes in energetic physiology that would be reflected in SMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation